Improvement of Engineering Properties of Residual Soil of Tuff Breccia by Electro-Kinetic Method - Doni Prakasa Eka Putra; Hnin Thazin Aung; I Gde Budi Indrawan (Geological Engineering Department Universitas Gadjah Mada, 2018)
This paper presents the results of an experimental study that was conductedto improve engineering properties of residual soil of tuff breccia by applying the electrokinetic method. The soil samples were taken from a slope in a high susceptible landslide area in the Kulon Progo, Yogyakarta, Indonesia. The electro-kinetic experiments were conducted using a clear glass tank of 60 cm 30 cm 30 cm size, a 13 V power pack to supply the voltage, and aluminum electrodes. The results showed that the pH value of anolyte decreased while that of catholyte increased during the treatment. The Atterberg’s limits of all soil samples decreased, while the shear strengths increased. XRD and SEM analyses indicated that there were no mineral changes after electro-kinetic experiments. However, the soil structure changed and became denser. The increased soil strength after electro-kinetic treatment would likely improve stability of natural slopes.